2016
DOI: 10.25311/keskom.vol3.iss2.110
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Penambahan Karbon Aktif Cangkang Kelapa Sawit (Elaeis Guineensis) dalam Proses Filtrasi Air Sumur

Abstract: Dampak dari pencemaran air dapat menyebabkan terjadinya ketidakseimbangan ekosistem dan dapat sebagai pembawa penyakit menular. Oleh karena itu perlu dilakukan penjernihan terhadap air sebelum digunakan untuk meningkatkan kualitas air.  Salah satu  yang dapat digunakan untuk penjernihan air adalah arang aktif cangkang kelapa sawit (Elaeis guineensis). Tujuan penelitian ini adalah: Untuk mengetahui efektifitas penambahan arang aktif cangkang kelapa sawit  dalam proses  filtrasi terhadap karakter fisik (kekeruha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…Based on the results of processing carried out in the absence of biofilm, only applying adsorption with filter media in the reactor has not met the quality standards for COD parameters according to regulations and from these results it can be concluded that biofilm serves to degrade organic levels in water (Fadhillah and Wahyuni, 2016).The efficiency of reduce COD levels continues to reduce over time which indicates the filter media has reached the optimum point so that it is necessary to wash the media again this is in accordance with the Sulistyanti experiment (2018) controlled flow velocity at a point will occur decrease back after reaching the optimum point to decompose organic compounds in wastewater (Ramdja et al, 2008). Reduction TSS levels TSS concentration of 407 mg/l, has efficiency removal of TSS levels reached 79% in the 70 minute so that the treatment of rubber wastewater has an optimum point in the 70 minute.…”
Section: Analysis Of Cod and Tss Levels Reduction Efficiencymentioning
confidence: 99%
“…Based on the results of processing carried out in the absence of biofilm, only applying adsorption with filter media in the reactor has not met the quality standards for COD parameters according to regulations and from these results it can be concluded that biofilm serves to degrade organic levels in water (Fadhillah and Wahyuni, 2016).The efficiency of reduce COD levels continues to reduce over time which indicates the filter media has reached the optimum point so that it is necessary to wash the media again this is in accordance with the Sulistyanti experiment (2018) controlled flow velocity at a point will occur decrease back after reaching the optimum point to decompose organic compounds in wastewater (Ramdja et al, 2008). Reduction TSS levels TSS concentration of 407 mg/l, has efficiency removal of TSS levels reached 79% in the 70 minute so that the treatment of rubber wastewater has an optimum point in the 70 minute.…”
Section: Analysis Of Cod and Tss Levels Reduction Efficiencymentioning
confidence: 99%
“…Elektrolisis memiliki adanya anion dan kation dalam larutan yang dapat bergerak dan dipisahkan dalam proses reduksi dan oksidasi, sehingga efisiensi perlakuan dapat meningkat. Sebelum air dapat digunakan, maka diperlukan adanya penjernih air dengan fungsi agar kualitas air dapat meningkat salah satunya dapat menerapkan penjernihan berupa disinfeksi (Fadhillah & Wahyuni, 2016).…”
Section: Pendahuluanunclassified
“…Arang aktif digunakan sebagai bahan penghilang warna keruh, bau tidak sedap, dan resin pada air dalam rumah tangga 10 . Mengenai proses filtrasi dengan penambahan arang aktif kelapa sawit ketebalan 10 cm dan 15 cm mampu menghilangkan bau pada air sumur 11 .…”
Section: Pendahuluanunclassified